2016
DOI: 10.1136/bjsports-2015-095951
|View full text |Cite
|
Sign up to set email alerts
|

Injury recurrence is lower at the highest professional football level than at national and amateur levels: does sports medicine and sports physiotherapy deliver?

Abstract: 258 words 3 ABSTRACTBackground Previous injury is a well-documented risk factor for football injury. The time-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(144 citation statements)
references
References 42 publications
9
106
1
5
Order By: Relevance
“…In the last few years, these percentages have been reduced as a result of the detailed knowledge now available about injuries and recovery (36).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, these percentages have been reduced as a result of the detailed knowledge now available about injuries and recovery (36).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, activities to prepare players for the running-based demands of Gaelic football should be investigated, particularly for players returning from injury. Recurrent hamstring injuries are also common in elite Australian football (20%), elite soccer (16–23%) and subelite soccer (12.5%) 7 14. Thus, higher recurrence rates in elite Gaelic football when compared with other field sports suggests some rehabilitation programmes are limited in facilitating complete recovery.…”
Section: Discussionmentioning
confidence: 99%
“…From this thesis and other previous publications, it seems clear that players are at increased risk of injuries as they RTS [10,46,48,49]. This could be an indication that the RTS criteria that are currently used in professional football do not provide sufficient information about whether players can return to football without sustaining a subsequent injury [51].…”
Section: Injury Risk After Rtsmentioning
confidence: 82%
“…Although there are important positive effects on an individual's health when playing football, there is also a substantial risk of sustaining injuries, especially among professional football players [10]. It has been shown that professional football is associated with a more than 1000-fold higher injury rate than other professions often considered to be high risk, such as manufacturing and construction [11].…”
Section: The Health Paradox In Sportsmentioning
confidence: 99%
See 1 more Smart Citation